FAKTOR-FAKTOR YANG MEMPENGARUHI POLA SPASIAL PERMUKIMAN SUKU BAJO DI DESA TOROSIAJE LAUT - Saman, Satar; Siola, Amru (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This research aims to determine the factors that influence spatial settlement patterns, because a deep understanding of these factors can help in the planning and management of sustainable coastal areas. Settlement area, is a place to live and a place to carry out activities to support the lives of its inhabitants, namely the relationship between humans and humans, with nature and with their creator. This research uses a rationalistic method, the analysis is done in qualitative description. The number of samples in this study were: 30 residential units of the Bajo tribe, from the total population of 112 residential units of the Bajo tribe that were found (remaining). Factors affecting the spatial pattern of settlements in the Bajo Tribe of Torosiaje Laut village, Poguwato district, the existence of geometric patterns that stand out in the main bridge network and the mass order of buildings is inseparable from natural factors in the form of the sea or tides. Patterns are seen in the mass order and network of main bridges and divider bridges. There is a short branching pattern. The smallest network is within the settlement area. Linear patterns are seen in the building mass order and bridge network in the eastern region, while the organic pattern factor is seen in the building mass order, and the connecting bridge network that develops due to spontaneity and irregularity of the building mass due to lack of planning.